Efficacy of alternative cooling devices used for insulin storage without refrigeration under hot-humid environment - Supang Taerahkun (2022)
Background: Insulin is temperature sensitive as high temperatures reduce its potency. Refrigeration for insulin storage is still needed but households in remote areas do not have refrigerators. Also, the electricity supply is usually affected by natural disasters. We aim to examine the temperature-reducing efficacy of cooling devices in hot-humid conditions. Methods: Five cooling devices, (1) earthen jar filled with water, (2) earthen jar filled with soil, (3) two clay pots, gap filled with wet soil, (4) two clay pots, gap filled with wet sand, and (5) commercial cooling wallet were used in this study. External and internal temperatures were monitored by the temperature logger between October 2019 and September 2020 in Narathiwat, Thailand. Cooling efficacy was assessed by average absolute temperature reduction and relative cooling effect. Results: Mean external temperature and humidity were 27.3 ± 1.5 °C and 78.2 ± 7.1%RH. The mean differences between the external and internal temperatures were; device (1) −0.1 ± 0.6 °C (p = NS), (2) 0.0 ± 0.8 °C (p = NS), (3) −1.7 ± 0.9 °C (p <.0001), (4) −2.0 ± 0.9 °C (p <.0001), and (5) −1.8 ± 0.9 °C (p <.0001). Device no. 3, 4, and 5 achieved a constant temperature reduction. The most efficacious device was device no. 4 with a relative cooling effect of 63.6% better than the cooling wallet (57.7%, p =.003). All devices were more efficacious at lower humidity levels. Conclusions: Traditional low-cost devices, such as clay pots, reduce storage temperatures to or close to room temperature in hot-humid climates. This study provides some guidance for insulin storage in hot-humid environments.